Maternal restrictive feeding practices for child weight control and associated characteristics - Fabrícia R. Freitas; Denise E.B. Moraes; Sarah Warkentin; Laís A. Mais; Júlia F. Ivers; José Augusto A.C. Taddei (Brazilian Society of Pediatrics, 2019)
Objective: To identify associations between maternal restrictive feeding practices for child weight control and sociodemographic, behavioral, dietetic, and anthropometric characteristics. Methods: Cross‐sectional study with mothers of children aged 2-8 years. Maternal feeding practices were measured by the Comprehensive Feeding Practices Questionnaire, in private schools in Brazil. Bivariate and multivariate associations were performed, using nonparametric analyses to estimate odds ratios and significance levels. Results: Maternal restrictive feeding practices for weight control were independently associated with the mother's perception of her child being a little overweight/overweight/obese (OR = 4.61, p = 0.001), greater concern about the child's overweight (OR = 2.61, p < 0.001), child's overweight/obesity/severe obesity (OR =  2.18, p < 0.001), and the child's greater intake of ultra‐processed foods (OR = 1.40, p = 0.026). Conclusion: In this study, the risk variables identified for the use of the maternal restrictive feeding practices to control the child's weight can be used to provide education and guidance interventions in health and education networks directed to groups with similar characteristics to those of the studied population. Resumo: Objetivo: Identificar associações da prática alimentar materna de restrição para controle de peso do filho com características sociodemográficas, comportamentais, dietéticas e antropométricas. Métodos: Estudo transversal com mães de crianças de dois a oito anos. Práticas maternas foram mensuradas por meio do instrumento Comprehensive Feeding Practices Questionnaire, em escolas privadas no Brasil. Para testar associações univariadas e múltiplas, foram feitos testes não paramétricos para cálculo de razões de chance (OR) e níveis de significância (valor de p). Resultados: A restrição materna para controle do peso da criança foi independentemente associada com a percepção de que seu filho está um pouco gordo/gordo/muito gordo (OR = 4,61, p = 0,001), a preocupação quanto ao excesso de peso infantil (OR = 2,61, p < 0,001), e em relação às características da criança, com o sobrepeso/obesidade/obesidade grave (OR = 2,18, p < 0,001) e o consumo de alimentos ultraprocessados (OR = 1,40, p = 0,026). Conclusão: Neste estudo as variáveis de risco identificadas para o uso da prática materna de restrição para controle de peso do filho podem ser usadas para direcionar ações de educação e orientação nas redes de saúde e ensino, dirigidas a grupo com características similares às da população estudada. Keywords: Obesity, Child, Body weight, Feeding behavior, Maternal behavior, Feeding practices, Palavras‐chave: Obesidade, Criança, Peso corporal, Comportamento alimentar, Comportamento materno, Práticas alimentares